HUBUNGAN ANTARA KEKUATAN OTOT LENGAN DAN KOORDINASI MATA TANGAN DALAM KEMAMPUAN PASSING BAWAH PERMAINAN BOLA VOLI PADA SISWA KELAS IX SMP NEGERI 2 CENRANA - Mohammad Idrus Agus; Rahmat Ilahi; Andi Mutmainna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the relationship between arm muscle strength and hand-eye coordination on volleyball underpassing ability among ninth-grade students of SMP Negeri 2 Cenrana. This study used a quantitative approach with a correlational design. The population consisted of 32 students, and all population members were selected as the sample using total sampling technique. The research instruments included a push-up test to measure arm muscle strength, a volleyball throw-and-catch test to measure hand-eye coordination, and an underpassing test to measure underpassing ability. Data were analyzed using descriptive and inferential statistics with SPSS version 27. Since the data were not normally distributed based on the Shapiro-Wilk test, Spearman Rank correlation and multiple regression analyses were applied. The results showed that there was no significant relationship between arm muscle strength and underpassing ability, with a correlation coefficient of 0.235 and significance value of 0.196 > 0.05. There was a significant relationship between hand-eye coordination and underpassing ability, with a correlation coefficient of 0.569 and significance value of 0.001 < 0.05. Simultaneously, arm muscle strength and hand-eye coordination had a significant relationship with underpassing ability, with a significance value of 0.030 < 0.05 and a contribution of 21.5%. It can be concluded that hand-eye coordination has a more dominant relationship with underpassing ability than arm muscle strength.